Some Records of grasshoppers (Pyrgomorphidae, Tetrigidae , Dericorythidae, Acrididae) of Baluchistan housed at National Insect Museum, Pakistan - Waheed Ali Panhwar; Ahmed Zia; Anjum Shehzad; Shahrukh Soomro; Muhammad Inam; Noor Ahmed Noonari (نامه انجمن حشره‌شناسی ایران)
Grasshoppers recorded before and after partition of Pakistan that are housed at National Insect Museum, Islamabad were examined during the present study. The examined material has never been published, especially grasshoppers group from this museum. A record of 24 species and subspecies, 21 genera falling in the 04 families’ i-e: Pyrgomorphidae, Tetrigidae, Dericorythidae, and Acrididae from only Baluchistan province has been presented in this paper. Some of the specimens were unidentified and some found with old names are identified with their valid species or subspecies names. The species Tenuitarsus angustus (Blanchard, 1836), Dericorys annulata (Fieber, 1853), Gonista rotundata Uvarov, 1933, Pyrgodera armata (Fischer von Waldheim, 1820) and Tropidopola longicornis syrica (Walker, 1871) are first time recorded from Baluchistan Pakistan. Pyrgodera armata (Fischer von Waldheim, 1820) is first time recorded from Pakistan making an addition to the list of grasshoppers of Pakistan. Many species distribution has been extended to new localities of Baluchistan Province of Pakistan.